Acoustic Emission: Standards and Technology Update 1999
DOI: 10.1520/stp15778s
|View full text |Cite
|
Sign up to set email alerts
|

A Proposed Standard for Evaluating Structural Integrity of Reinforced Concrete Beams by Acoustic Emission

Abstract: A series of studies has been performed to evaluate the structural integrity of reinforced concrete (RC) beams by acoustic emission (AE). Cyclic loadings were applied to RC beams with a single reinforcing bar, large repaired beams, beams deteriorated due to corrosion of reinforcement, and two beams with different damage levels in an aging dock. The test results demonstrated that the Kaiser effect starts to break down when shear cracking starts to play a primary role. It has been also shown that high AE activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…AE monitoring experiments were performed successfully under incremental cyclic loading of RC beams with different percentage of reinforcement using AE energy parameter. By defining two ratios, namely, calm ratio and load ratio based on AE energy and Kaiser effect, the state of damage in RC beams was investigated [19,20]. A damage assessment chart was made using load ratio, calm ratio parameters and linking them to the crack mouth opening displacement (CMOD) [20].…”
Section: Ae Energy Analysismentioning
confidence: 99%
“…AE monitoring experiments were performed successfully under incremental cyclic loading of RC beams with different percentage of reinforcement using AE energy parameter. By defining two ratios, namely, calm ratio and load ratio based on AE energy and Kaiser effect, the state of damage in RC beams was investigated [19,20]. A damage assessment chart was made using load ratio, calm ratio parameters and linking them to the crack mouth opening displacement (CMOD) [20].…”
Section: Ae Energy Analysismentioning
confidence: 99%
“…For acoustic emission evaluation, several investigators have reported correlation of AE parameters to damage levels of reinforced concrete structures. One of the most widely implemented damage assessment methods is the correlation of calm ratio and load ratio (also referred to as Felicity ratio) (Yuyama et al, 1999;JSNDI, 2000). Another approach makes use of severity versus historic index, known as 'Intensity Analysis', as a measure of deterioration for concrete bridges .…”
Section: Reinforced Concretementioning
confidence: 99%
“…The method involves performing comparative analysis of the acoustic emission signals recorded during the tests and those collected in the database of reference signals corresponding to particular destructive processes. The results are used to identify and locate active destructive processes in reinforced concrete structures (IADP-Identification of Active Damage Processes), in prestressed concrete structure (RPD-Recognition of Destructive Processes), and in steel structures, thereby allowing the global monitoring across the whole member and recording only active deterioration processes developing under actual loading conditions [7][8][9][10][11][12][13][14][15][16][17]. The AE method is being increasingly developed for use in the construction of gas pipelines.…”
Section: Introductionmentioning
confidence: 99%